丹戎布拉大学师范教育学院汉语教育专业2018届学生 使用“不”和“没有”的偏误分析 - Elizabeth Elizabeth; Lily Thamrin; Lusi Lusi (Universitas Tanjungpura, 2022)
AbstractIn terms of learning Mandarin, the negative adverb are one of the most commonly used adverbs in Mandarin expressions. It is also the focus and difficulty in Mandarin teaching. Take mandarin negative adverb “bu”and “meiyou”as examples,these two words are the most commonly used words in daily life. Their similarities and differences in meaning make students often make a mistakes. To analyze the error analize usage of negative adverb “bu”and “meiyou” of the Mandarin language programme students batch 2018 in Faculty of Teacher Education and Education Science Tanjungpura University, the writer used research test method to collect the data. The result of this paper shows the analyze the error analize usage of negative adverb “bu”and “meiyou” of the Mandarin language programme students batch 2018 in Faculty of Teacher Education and Education Science Tanjungpura University is 82.79% and 54.3%. The reason why students make mistakes in using the negative adverb “bu”and “meiyou”is because of the native language. The writer hopes this research can be a reference to help the students that learns Mandarin as their second language.